2007
DOI: 10.4161/cc.6.23.4949
|View full text |Cite
|
Sign up to set email alerts
|

ErbB-2 Receptor Cooperates with E6/E7 Oncoproteins of HPV Type 16 in Breast Tumorigenesis

Abstract: Previously published online as a Cell Cycle E-publication: http://www.landesbioscience.com/journals/cc/article/4949 KEY woRDsBreast tumorigenesis, transgenic mice, ErbB-2 and E6/E7 of high-risk HPV ACKnowlEDGEMEnTsWe are grateful to Drs G. Batist, M. AlaouiJamali and Foulkes for their support of this work. We are thankful to Dr. A. Darnel for his critical reading of the manuscript. We also thank Dr. T. Li-Qun and G. Mousavi for their technical assistance. This work is supported by the Canadian Institutes for H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 24 publications
0
21
0
1
Order By: Relevance
“…In parallel, we revealed that D-type cyclins (D1, D2, and D3) are essential for cell transformation induced by E6/E7/ ErbB-2 cooperation in human HNE and mouse normal embryonic fibroblast (NEF) cells [96,97]. Finally, we were able to show that the cooperation effect of E6/E7 with ErbB-2, in human normal epithelial and cancer cells, occurs via β-catenin tyrosine phosphorylation through pp60 (c-Src) kinase activation [98,99]. Thus, the cooperation between E6/E7 oncoproteins of highrisk HPVs and other oncogenes could occur in colorectal carcinogenesis.…”
Section: High-risk Hpvs In Colorectal Cancersmentioning
confidence: 55%
“…In parallel, we revealed that D-type cyclins (D1, D2, and D3) are essential for cell transformation induced by E6/E7/ ErbB-2 cooperation in human HNE and mouse normal embryonic fibroblast (NEF) cells [96,97]. Finally, we were able to show that the cooperation effect of E6/E7 with ErbB-2, in human normal epithelial and cancer cells, occurs via β-catenin tyrosine phosphorylation through pp60 (c-Src) kinase activation [98,99]. Thus, the cooperation between E6/E7 oncoproteins of highrisk HPVs and other oncogenes could occur in colorectal carcinogenesis.…”
Section: High-risk Hpvs In Colorectal Cancersmentioning
confidence: 55%
“…The results of other authors investigating E-cadherin involvement in brain metastasis (Arnold et al, 1999;Shabani et al, 2003;Prudkin et al, 2009) collectively demonstrate that Ecadherin is constantly expressed in metastatic deposits. Furthermore, our recent studies also demonstrated that E-cadherin-catenin complex is involved in cell migration and metastasis in vivo and in vitro (Yasmeen et al, 2007). In order to investigate the cooperation effect between ErbB-2 receptor and high-risk human papillomavirus (HPV) in breast carcinogenesis and metastasis, we generated double transgenic mice carrying ErbB-2 and E6/E7 of HPV type 16 under mouse mammary tumour virus (MMTV) and human keratin 14 (K14) promoters, respectively.…”
Section: Mmps and E-cadherin In Brain Metastasismentioning
confidence: 99%
“…Histological analysis of ErbB-2/E6/E7 transgenic mouse tumours revealed the presence of invasive breast carcinomas. However, breast tissues from ErbB-2 and E6/E7 singly transgenic mice showed only in-situ cancer and normal mammary phenotype, respectively (Yasmeen et al, 2007). In parallel, to assess the outcome of ErbB-2/E6/E7 cooperation in human breast carcinogenesis, we examined the effect of ErbB-2 and E6/E7 of HPV type 16 on the BT20 breast cancer cell lines.…”
Section: Mmps and E-cadherin In Brain Metastasismentioning
confidence: 99%
See 2 more Smart Citations